O ensino de Filosofia e a criação de conceito: uma proposta metodológica a partir das imagens do livro didático do ensino médio - TRINDADE , José Raimundo (2021)
The present work is the result of a research about the importance of using pictures how a methodological resource for the teaching of philosophy, at the high school. It is a qualitative research with ethnographic elements, which uses participant observation and questionnaire application of data collection tools. From a theoretical point of view, it is based on the philosophical conception of Deleuze and Guattari (1992) according to which, philosophy consists of creating concepts and the method of teaching philosophy proposed by Gallo (2012), composed of four didactic steps: awareness, problematization, investigation and conceptualization. From the methodological point of view, it is based on Ludke and André (1986), Ferrarotti (2010), Angrossino (2009), Lima (2006), Souza (2006ª, 2016b, 2008) among others. The work is divided at three chapters. The first chapter is dedicated to teaching philosophy while concept workshop. The second is dedicated to the investigation of picture how methodological tool for the teaching of philosophy. The third chapter presents the practical part of the research and deals with how you can teach philosophy from the pictures of the textbook in high school. For this, it presents two didactic sequences that will be applied to the students of the second year of High School, at the Centro de Ensino Mário Martins Meireles, in São Luís - Ma.